Genetic Variability And Association Studies Among Yield Contributing Traits In Gladiolus (Gladiolus Hybridus Hort.) Under Sub-Tropical Conditions Of Punjab (India) (Applied Biological Research, 2014)
Fifty seven genotypes of gladiolus were assessed for their efficiency with  respect to yield and its contributing traits at PAU Ludhiana (Punjab). The  higher PCV and GCV estimates were observed for the number of cormels  plant-1, weight corm-1and polar diameter of corm. High heritability with  high genetic advance was registered for weight corm-1, spike length,  number of cormels plant-1, days taken to heading and days taken to open  1st floret. The correlation studies revealed strong positive association of the  number of florets spike-1 with the number of leaves, flower duration, spike  length, spike diameter, weight corm-1, polar diameter of corm and number  of cormels plant-1at both phenotypic and genotypic level. The path  analysis indicated that spike length followed by polar diameter of corm and flower duration had highest magnitude of positive direct effect on the number of florets spike-1at phenotypic level, while polar diameter of corm  followed by spike length and flower duration had highest direct effect on  the number of florets spike-1at genotypic level.
Keywords: Association; gladiolus; genetic variability; path coefficient